Knowledge-based and intelligent information and engineering systems 15th International Conference, KES 2011, Kaiserslautern, Germany, September 12-14, 2011, proceedings Part I - International Conference on Knowledge-Based Intelligent Information and Engineering Systems 2011 Kaiserslautern, Germany); Konig, Andreas; Dengel, Andreas; Hinkelmann, Knut.; Kise, Koichi; Howlett, Robert J.; Jain, Lakhmi C.; SpringerLink (Online service). (Berlin New York Springer, 2011)
The four-volume set LNAI 6881- LNAI 6884 constitutes the refereed proceedings of the 15th International Conference on Knowledge-Based Intelligent Information and Engineering Systems, KES 2011, held in Kaiserslautern, Germany, in September 2011.
Electronic reproduction.
Keywords: Expert systems (Computer science) -- Congresses; Data mining -- Congresses; Electronic books